Sensitivity of Beech Trees to Global Environmental Changes at Most North-Eastern Latitude of Their Occurrence in Europe - Algirdas Augustaitis; Dalia Jasineviciene; Rasele Girgzdiene; Almantas Kliucius; Vitas Marozas (The Scientific World Journal)
The present study aimed to detect sensitivity of beech trees (Fagus sylvatica L.) to meteorological parameters and air pollution by acidifying species as well as to surface ozone outside their north-eastern distribution range. Data set since 1981 of Preila EMEP station enabled to establish that hot Summers, cold dormant, and dry and cold first-half of vegetation periods resulted in beech tree growth reduction. These meteorological parameters explained 57% variation in beech tree ring widths. Acidifying species had no significant effect on beech tree growth. Only ozone was among key factors contributing to beech stand productivity. Phytotoxic effect of this pollutant increased explanation rate of beech tree ring variation by 18%, that is, up to 75%. However, due to climate changes the warmer dormant periods alone are not the basis ensuring favourable conditions for beech tree growth. Increase in air temperature in June-August and decrease in precipitation amount in the first half of vegetation period should result in beech tree radial increment reduction. Despite the fact that phytotoxic effect of surface ozone should not increase due to stabilization in its concentration, it is rather problematic to expect better environmental conditions for beech tree growth at northern latitude of their pervasion.